2021
DOI: 10.35311/jmpi.v7i1.72
|View full text |Cite
|
Sign up to set email alerts
|

Studi Etnomedisin Tanaman Berkhasiat Obat Hipertensi di Kecamatan Poleang Tenggara Kabupaten Bombana Sulawesi Tenggara

Abstract: Etnomedisin merupakan salah satu cara yang dapat digunakan untuk mendokumentasikan pemanfaatan tumbuhan sebagai bahan obat. Tujuan dari penelitian ini adalah untuk mengetahui jenis tanaman yang digunakan sebagai obat untuk hipertensi, mengetahui bagian tanaman yang digunakan sebagai obat hipertensi dan bagaimana cara pengolahan tanaman obat yang digunakan untuk mengobati hipertensi di Kecamatan Poleang Tenggara Kabupaten Bombana. Jenis penelitian ini adalah penelitian deskriptif dengan analisis data menggunaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…However, our result differs from research by Shedoeva et al (2019), which found that the whole plant and stem parts are the most widely used. Leaves are used in medicine because they are the easiest to obtain, so they are often consumed by the community, especially in the tropics (Saranani et al 2021). The leaves have effective chemical ingredients in curing various diseases (Irawati et al 2018).…”
Section: %mentioning
confidence: 99%
See 1 more Smart Citation
“…However, our result differs from research by Shedoeva et al (2019), which found that the whole plant and stem parts are the most widely used. Leaves are used in medicine because they are the easiest to obtain, so they are often consumed by the community, especially in the tropics (Saranani et al 2021). The leaves have effective chemical ingredients in curing various diseases (Irawati et al 2018).…”
Section: %mentioning
confidence: 99%
“…The leaves contain many secondary metabolites such as essential oils, flavonoids, alkaloids, steroids, and triterpenoids to be natural medicines (Albayudi and Saleh 2020). The leaves also have soft fibers that can be processed by various methods (Saranani et al 2021).…”
Section: %mentioning
confidence: 99%
“…Sebaliknya, patah tulang pada anak-anak cenderung mudah disembuhkan (<1 bulan) dengan faktor tulang anak yang lebih banyak mengandung zat perekat atau kolagen sehingga membantu proses penyembuhan patah tulang pada anak. Di sisi lain, jenis dan kondisi patah tulang pun mempengaruhi proses penyembuhan karena membutuhkan kesabaran dan keyakinan dari kita terhadap penyehat yang dipercayai untuk menyembuhkan patah tulang [26][27][28][29].…”
Section: Pengolahan Tumbuhan Obat Tradisional Patah Tulang Bagi Masya...unclassified
“…According to Fanani et al, (2018), the investigation of wild plants utilized in ethnomedicine constitutes an integral component of herbal medicine research, and the identification of medicinal plants is a critical step in the formulation of such remedies to guarantee the accuracy of the plant species employed. Saranani et al, (2021) conducted research in the Regency of Bombana, Poleang Tenggara Subdistrict, Southeast Sulawesi, which identified twenty species of medicinal plants utilized for the treatment of hypertension; the most commonly utilized plant parts are fruits, leaves, rhizome seeds, and herbs. The current state of ethnomedicine research in Aceh is significantly limited.…”
Section: Introductionmentioning
confidence: 99%